Pendekatan Pastoral Konseling dalam Mendampingi Seorang Ibu dengan Gerd Anxiety - Frenty Sariyati; Rencan Carisma Marbun (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
GERD anxiety is a combination of GERD (Gastroesophageal Reflux Disease) or a stomach acid disorder characterized by a burning sensation in the chest and solar plexus area and also a mental disorder called anxiety or anxiety disorder. Apart from medical treatment, GERD anxiety sufferers must receive spiritual treatment. In this case, pastoral counseling can meet the needs of GERD anxiety sufferers in spiritual treatment. Gerd anxiety is a disease that must be treated immediately because if it is not treated it will worsen the sufferer's condition and can even make it difficult for sufferers to carry out activities and socialize, and can also reduce the sufferer's quality of life. This research uses a qualitative approach with a case study method. This research was aimed at a mother who suffered from GERD anxiety for almost two years. The research was carried out using a pastoral counseling process carried out by church ministers during several meetings. The results show that the pastoral counseling approach can complement medical assistance for GERD anxiety sufferers and is an effective aid for recovering sufferers.